PERTUMBUHAN IKAN TERBANG (Hirundichthys oxycephalus) DI FERAIRAN BINUANGEUN, BANTEN [Growth of Flying Fish (Hirundichthys oxycephalus) in Binuangeun Waters, BantenJ - Tanti SR Harahap; A. Djamali (Jurnal Iktiologi Indonesia, 2005)
The research was conducted from June to September 2005 was aimed to describe the growth of flying fish (Hirundichthys oxycephalus). Fish sample that were taken from capture of local fishermen. Laboratory analysis included fish identification, measurement of total length and weight. Data analysis included length frequency, growth parameter, length weight relationship and condition factor. The number of sample fish was 242, which total length ranged 214.5 - 278.5 mm. The von Bertalanffy growth equation was Lt = 321.13(1-e -0.1514(L+0.5875)). Male and female grow'th model is negative allometric, and the equations were W = 0.0003 L 2.2877 and W = 0.002 L 1.9579 consecutively. Weight growth model of von Bertalanffy was: Wt = 167.57 (1 - e-0.1514 (1+0.5875)) 2.2042. The average of condition factor male ranged from 1.05 - 1.18 while female ranged from 0.97 - 1.10. The highest condition factor of male occurred at June (1.18) while female at August (1.10).